Understanding the Interplay of Religion and Social Policy: Challenges and Opportunities - Nur, Mohamad Ichsana (FISIP UIN Sunan Gunung Djati Bandung, 2023)
Research Problem: This research explores the complex dynamics between religion and social policy, highlighting the challenges and opportunities that arise from these interactions. The focus is on the influence of religious meaning systems at the individual, group, community and societal levels. Research purposes: The aim of this research is to discover how wise policy implementation can optimize the positive role of religion in prevention, healing, group empowerment, and increasing community capacity, as well as to identify critical challenges that may be faced in the process. Research methods: This research uses a qualitative approach with in-depth research methods that include positive and negative aspects of the influence of religion. Collaboration between policy makers, psychologists, and religious institutions is considered important in overcoming the identified barriers. Results and Discussion: The research results show that wise policy implementation can optimize the role of religion in various aspects of people's lives. However, challenges such as the constitutional separation between religious institutions and the state, incompatibilities in systems of meaning, and the complexity of religious beliefs are also identified. Research Implications and Contributions: This research provides better insight into how policy can be an effective tool in strengthening societal welfare by wisely integrating religious values. The findings of this research build a bridge between the complex interactions of religion and policy, while highlighting the potential for constructive collaboration that can have a positive impact on society at large.